RUANG SAKRAL-PROFAN PADA MASJID JAMI' PITI MUHAMMAD CHENG HOO PURBALINGGA - Fadhilah Siti Aniisah Haryono; Muhammad Nur Hakimuddin At-toyibi (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The conception of sacred and profane space, pioneered by Durkheim and Eliade, is a fundamental dichotomy where the sacred space is a separate, consecrated domain that serves as a locus for transcendent manifestation, while the profane space is the ordinary, mundane world. In Javanese mosque architecture, this dichotomy is manifested through a tiered spatial hierarchy comprising the sacred core space that requires the highest purity for ritual worship, the transitional/buffer space that mediates worldly activities supporting the worship, and the External Profane Space for purely socio-economic activities. Masjid Jami' PITI Muhammad Cheng Hoo Purbalingga replicates this functional hierarchy, yet it utilizes Chinese acculturation as a visual-cultural marker in its profane and transitional zones. Conversely, the sanctity of its core space is strictly maintained by universal Islamic theological markers (such as calligraphy and Qibla orientation), making it a model of inclusivity that expands the boundaries of profanity for both cultural and functional accommodation.